Update on the Use of Inhaled Nitric Oxide - Robert M Kacmarek (Canadian Respiratory Journal)
A literature review on nitric oxide would identify thousands of citations on the biological implications of this molecule. From the perspective of respiratory care, the effect inhaled nitric oxide has on pulmonary vasculature is the most intriguing. Over the past five years inhaled nitric oxide has been shown to be useful in the management of oxygenation during acute respiratory distress syndrome, alternation of pulmonary vascular tone in persistent pulmonary hypertension in the newborn, and in the management of chronic pulmonary hypertension in both heart and lung transplant candidates, as well as other potential clinical uses. The key physioligical response is vasodilation of pulmonary vessels in communication with well ventilated lung units and the absence of systemic vascular effects by rapid binding to hemoglobin. Nitric oxide therapy is considered experimental. A delivery system is not commercially available. This has resulted in the development of makeshift delivery systems, many of which may have the potential for adverse effects.